Climate action and creative climate justice - Erlend Eggen; Lise Hovik (Nordic Journal of Art and Research, 2023)
The answer to SDG 13 Climate action in this special issue takes the form of a contribution that breaks with the academic genre and bypasses the established academic or artistic formats of the journal. Instead, this contribution opens the door to the climate activist movement, shining a light on the urgency of the hour and the issues that are paramount in the hearts of climate-engaged artists, educators and cultural workers. Klimakultur, a non-profit organization supporting and strengthening the climate and environmental ambitions of the arts and culture sector in Norway, has together with Rosendal Teater in Trondheim released what they call a Creative Climate Justice Guide. This publication serves as inspirational tool for climate action.